The business models handbook : templates, theory and case studies - Hague, Paul N. (Koganpage, 2019)
Business frameworks sit at the heart of every successful business. They add structure and clarity to business problems and can help practitioners overcome the everyday challenges they face. The Business Models Handbook brings together the most helpful and widely used templates and frameworks into a single, invaluable resource. Each chapter focuses on an individual business framework, giving an overview of 50 of the best known frameworks and how it will help an organization grow and be profitable. Each supported by a real-world case study, these include ANSOFF matrix, Price-Quality-Strategy model, Stage-Gate model, Service Profit Chain and many more.